Perceptions and Experiences of Frontline Urban Indian Organization Healthcare Workers With Infection Prevention and Control During the COVID-19 Pandemic - Collins, Noah; Crowder, Jolie; Ishcomer-Aazami, Jamie; Apedjihoun, Dionne (Frontiers in Sociology, 2021)
Coronavirus disease 2019 (COVID-19) has created significant challenges for outpatient healthcare providers and patients across the United States (U.S.). Forty-one Urban Indian Organizations (UIOs), who provide a wide spectrum of health services for American Indian and Alaska Native (AI/AN) populations and other underinsured and uninsured populations in urban areas across the country, are no exception. The National Council of Urban Indian Health (NCUIH), in collaboration with the U.S. Centers for Disease Control and Prevention (CDC), set out to understand the needs, challenges, and opportunities for improvement in infection prevention and control (IPC) training and systems from the perspective of UIO frontline healthcare workers. As part of the CDC's Project Firstline, NCUIH was chosen as a partner in a national collaborative. The first task was to conduct listening sessions with frontline UIO staff to learn more about IPC practices in the context of the COVID-19 pandemic. Thirty staff from 16 UIOs, representing full ambulatory, limited ambulatory, outreach and referral, and outpatient and residential treatment programs participated in virtual video focus groups in July of 2020. Thematic and content analysis protocols guided data analysis and coding. Analysis of findings generated four major themes: staff adaptation in the context of resilience; responsibility and duty to protect patients, families, and coworkers; mental and emotional issues for UIO staff; and IPC challenges in the context of COVID-19. Participants' challenges ranged from lack of access to personal protective equipment (PPE) to the absence of standardized training. Significant disparities in social determinants of health experienced by Native American and non-Native populations served by UIOs create additional challenges to the delivery of and access to care during the pandemic. The diverse array of tribal cultural values and contexts of the people and communities served by UIOs reportedly serve as both facilitators and barriers to care, awareness, and uptake of infectious disease public health practices.